A Modern Pedagogical Approach in The Subject of Physical Education - Cereda, Ferdinando (Physical Education and Sports: Studies and Research, 2023)
Background: The pedagogical paradigm (PP) is a complex framework encompassing various pedagogical elements integral to the instructional and educational process. These paradigms manifest in diverse forms without entirely replacing their precursor frameworks, as they are built upon established principles and concepts. Understanding the architectural structure of each paradigm is crucial in distinguishing these pedagogical models. Objective: This exposition aims to provide a rationale for the integration of the pedagogical paradigm within the realm of PE. Methods: In the literature review, the EBSCO database was utilized via SPORTDiscus. This theoretical review draws upon various scholarly sources, including Taylor and Francis, ERIC, Scopus, Google Scholar These repositories provide a global perspective, with the majority of references selected from the decade leading up to the onset of the pandemic. Results: The literature analysis reveals the intricate nature of pedagogical paradigms and their importance in the field of PE. It underscores the need for instructors to adapt their teaching approaches to meet the specific needs of students based on their age and developmental stage. The integration of the pedagogical paradigm within PE is proposed as a valuable concept to enhance the quality of physical education programs. Conclusion: The incorporation of the PP into the domain of PE holds promise for improving the effectiveness of PE instruction. This review, based on a thorough examination of pertinent literature, highlights the relevance of PP in adapting teaching methodologies to suit the diverse needs of students. While this study does not provide empirical evidence, it lays the theoretical groundwork for future research and practical applications in the field of PE. Further investigations and practical implementations are warranted to assess the feasibility and benefits of incorporating PP within PE instruction.